The Influence of Basic Education Teacher's Academic Qualifications in Developing Teacher Professionalism - Dwisari, Evi (Journal of Education Method and Learning Strategy, 2023)
This study aims to determine the effect of the academic qualifications of basic education teachers and the efforts that can be made in developing teacher professionalism. The method used in this research is ex post facto by taking data without providing accompanying treatment. The data taken is the academic qualifications of basic education teachers which are then used to determine the level of teacher professionalism. The level of basic education that is focused on in this study is the level of PAUD teachers in the Buleleng Regency area. The results of the study were that there were differences in the ability to assess PAUD teachers between groups of teachers who had graduated from PAUD, non-PAUD graduates, and teachers who had not graduated.